Biocontrol of Tomato Bacterial Wilt by Foliar Spray Application of a Novel Strain of Endophytic Bacillus sp. - Fu, Hui-Zhen (Microbes Environ, 2020)
The aim of the present study was to identify a strain of endophytic Bacillus species that control tomato bacterial wilt by foliar spray application. Fifty heat-tolerant endophytic bacteria were isolated from the surface-sterilized foliar tissues of symptomless tomato plants that had been pre-inoculated with the pathogen Ralstonia pseudosolanacearum. In the primary screening, we assessed the suppressive effects of a shoot-dipping treatment with bacterial strains against bacterial wilt on tomato seedlings grown on peat pellets. Bacillus sp. strains G1S3 and G4L1 significantly suppressed the incidence of tomato bacterial wilt. In subsequent pot experiments, the biocontrol efficacy of foliar spray application was examined under glasshouse conditions. G4L1 displayed consistent and significant disease suppression, and, thus, was selected as a biocontrol candidate. Moreover, the pathogen population in the stem of G4L1-treated plants was markedly smaller than that in control plants. A quantitative real-time PCR analysis revealed that the foliar spraying of tomato plants with G4L1 up-regulated the expression of PR-1a and LoxD in stem and GluB in roots upon the pathogen inoculation, implying that the induction of salicylic acid-, jasmonic acid-, and ethylene-dependent defenses was involved in the protective effects of this strain. In the re-isolation experiment, G4L1 efficiently colonized foliar tissues for at least 4‍ ‍weeks after spray application. Collectively, the present results indicate that G4L1 is a promising biocontrol agent for tomato bacterial wilt. Furthermore, to the best of our knowledge, this is the first study to report the biocontrol of bacterial wilt by the foliar spraying with an endophytic Bacillus species.